Simplifying
2ab + 4ab = 0
Combine like terms: 2ab + 4ab = 6ab
6ab = 0
Solving
6ab = 0
Solving for variable 'a'.
Move all terms containing a to the left, all other terms to the right.
Divide each side by '6'.
ab = 0
Simplifying
ab = 0
5x + 6 = 1
Subtract 6 from both sides.
5x = -5
Divide from both sides.
x = -1 (ANSWER)
hope this helps!!
Answer:
4(x+2) = 4x + 8
Step-by-step explanation:
because if they are multiplied out it would be 4x+8 = 4x + 8 which means it is infinite because both sides are equal
Answer: 28 in.
Step-by-step explanation:
its simple